Detection of spoofed and non-spoofed DDoS attacks and discriminating them from flash crowds - Jaideep Gera (EURASIP Journal on Information Security, 2018)
Abstract Distributed computing technology is widely used by Internet-based business applications. Supply chain management (SCM), customer relationship management (CRM), e-Commerce, and banking are some of the applications employing distributed computing. These applications are the main target to massive attacks known as distributed denial-of-service (DDoS) that cause a denial of service or degradation of services being rendered. The servers that provide reliable services to genuine users in a distributed environment are victims of such attacks that flood fake requests that appear genuine. Flash crowd, on the other hand, is the huge amount of traffic caused by certain flash events (FEs) that mimics DDoS attacks. Detection of DDoS attacks in the wake of flash crowds is a challenging problem to be addressed. The existing solutions are generally meant for either flash crowds or DDoS attacks and more research is needed to have a comprehensive approach for catering to the needs of detection of spoofed and non-spoofed variants of DDoS attacks. This paper proposes a methodology that can detect aforementioned DDoS attacks and differentiate them from flash crowds. NS-2 simulations are carried out on Ubuntu platform for validating the effectiveness of the proposed methodology.